2020
DOI: 10.1113/jp278827
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for temperature‐mediated regional increases in cerebral blood flow during exercise

Abstract: Key points Aerobic exercise elicits increases in cerebral blood flow (CBF), as well as core body temperature; however, the isolated influence of temperature on CBF regulation during exercise has not been investigated The present study assessed CBF regulation and neurovascular coupling during submaximal cycling exercise and temperature‐matched passive heat stress during isocapnia (i.e. end‐tidal PnormalCO2 was held constant) Submaximal cycling exercise and temperature‐matched passive heat stress provoked ∼16% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
(205 reference statements)
0
20
0
Order By: Relevance
“…2020; Caldwell et al . 2020) show little evidence of a decrease in CBF with passive increases in T c ranging from 0.7 to 2°C when decreases in PnormalETCO2 were mild or absent (Gibbons et al . 2019; Bain et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020; Caldwell et al . 2020) show little evidence of a decrease in CBF with passive increases in T c ranging from 0.7 to 2°C when decreases in PnormalETCO2 were mild or absent (Gibbons et al . 2019; Bain et al .…”
Section: Discussionmentioning
confidence: 99%
“…2020; Caldwell et al . 2020). However, the absence of a decrease in global CBF with heating is not universal (Nybo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric blood flow in the ICA, ECA and VA were determined by two separate investigators concurrently using duplex ultrasound (Vivid-i; GE Healthcare, Tokyo, Japan) equipped with a 10-13 MHz linear transducer. We and others have demonstrated that this approach is technically feasible and free of any potential confounds caused by probe positioning or competitive ultrasound beam interference (Caldwell et al, 2020;Hirasawa et al, 2016;Ogoh, Nakahara et al, 2014Sato et al, 2011). The ICA and ECA measurements were taken 1.0−1.5 cm distal to the carotid bifurcation on the right side of the neck, with the subject's chin slightly elevated.…”
Section: Cerebrovascular Functionmentioning
confidence: 99%
“…As previously shown by Caldwell et al . (2020), the isocapnic cerebral blood flow (CBF) response to passive heat and thermal strain‐matched exercise is similar, both in magnitude and in topography of distribution. This begs the question, at least in terms of cerebral blood flow regulation: is all heat equal?…”
mentioning
confidence: 99%
“…Although the isocapnic CBF response is comparable between thermally‐matched exercise and passive heating (Caldwell et al . 2020), the prevailing poikilocapnic CO 2 concentration will dictate the brain's environment, and most probably influence the adaptive stimulus. We suspect that there is a fine line between a beneficial adaptive stimulus and an acute cerebral insult, characterized by increased blood–brain barrier permeability, inflammation, oxidative stress and elevated intracranial pressure.…”
mentioning
confidence: 99%